Music therapy, sensory integration and the autistic child - Berger, Dorita S. (Jessica Kingsley Publishers, 2002)
Written in a way that is both informative for the professional and accessible for parents, this book furthers the already strong case for the use of music therapy as a resource to encourage behavioural changes for the better in children with autism spectrum conditions.